COMPARISON OF FUNCTIONAL OUTCOMES AFTER ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION - Uszko, Milena; Utnik, Martyna; Bajur, Patrycja; Czereczon, Wiktor; Działowy, Maksymilian (International Journal of Innovative Technologies in Social Science, 2026)
Background. In competitive athletes undergoing anterior cruciate ligament reconstruction (ACLR), bone–patellar tendon–bone (BPTB) and hamstring tendon (HT) autografts are the most common options. Clinically meaningful differences likely appear in return-to-sport/performance, graft survival, knee stability, and donor-site morbidity. Aim. To summarize 2021–2026 comparative evidence on BPTB versus HT in competitive/high-activity athletes after primary ACLR, focusing on return to sport/performance, patient-reported outcomes, function, stability, graft failure, and donor-site morbidity. Materials and methods. Narrative literature review of PubMed and Scopus, including reviews, observational studies, and clinically relevant case series. Results. Athlete-focused randomized and observational studies show generally similar outcomes between graft types at short- to mid-term follow-up. In professional/semi-professional soccer, RTS and knee-function scores were comparable at 2 years, but anterior knee pain was higher with BPTB (48.4%) than HT (22.6%). Large high-activity cohorts reported higher odds of return to preinjury activity with BPTB, though meta-analyses found no consistent difference across heterogeneous definitions. Instrumented laxity favored BPTB in athlete-focused syntheses and long-term cohorts, though surgical techniques may confound some findings. Several cohorts indicated higher ipsilateral graft failure/retear with HT in younger/high-risk athletes, while BPTB showed slower attainment of common early RTS strength/hop milestones. Conclusions. In competitive/high-activity athletes, BPTB is associated with lower graft failure risk and modestly better stability, counterbalanced by higher anterior knee pain and potentially slower early functional recovery.